2018
DOI: 10.7567/jjap.57.04fr07
|View full text |Cite
|
Sign up to set email alerts
|

Influence of basal-plane dislocation structures on expansion of single Shockley-type stacking faults in forward-current degradation of 4H-SiC p–i–n diodes

Abstract: The origin of expanded single Shockley-type stacking faults in forward-current degradation of 4H-SiC p-i-n diodes was investigated by the stresscurrent test. At a stress-current density lower than 25 A cm %2 , triangular stacking faults were formed from basal-plane dislocations in the epitaxial layer. At a stress-current density higher than 350 A cm %2, both triangular and long-zone-shaped stacking faults were formed from basal-plane dislocations that converted into threading edge dislocations near the interfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 31 publications
0
40
0
Order By: Relevance
“…The 1SSFs of T1 and T3 had a right-angled corner on the right side, and these two types are the most frequently observed and repo rted. 3,[5][6][7][9][10][11][12][13][14]16,[19][20][21][22] However, the 1SSFs of T2 had a triangular shape with a right-and-left in contrast to T1 and T3. The expansion direction of T2, which was from the surface to the substrate/epilayer interface, was opposite to that of T3.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…The 1SSFs of T1 and T3 had a right-angled corner on the right side, and these two types are the most frequently observed and repo rted. 3,[5][6][7][9][10][11][12][13][14]16,[19][20][21][22] However, the 1SSFs of T2 had a triangular shape with a right-and-left in contrast to T1 and T3. The expansion direction of T2, which was from the surface to the substrate/epilayer interface, was opposite to that of T3.…”
Section: Resultsmentioning
confidence: 93%
“…Additionally, it is reasonable that the J th of this BPD at a depth of 1.3 μm was not low but rather an intermediate value, because it has been reported that the J th is related to the depth of the BPD. 19 To confirm the core species directly and to determine the unique Burgers vectors of the PDs that make up the 1SSF, cross-sectional STEM analysis was employed, and the FIB sampling point and observation direction were selected, as indicated by the orange line and arrow in Fig. 4a.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent SiC epitaxial wafers, BPDs are mostly present in the substrates but not in the epilayers, owing to the conversion of BPDs to TEDs in the initial stage of epitaxial growth 20 24 . Therefore, a remaining issue for bipolar degradation is the expansion of BPDs in substrates 25 27 . Inserting a “recombination enhancing layer” between a drift layer and a substrate has been suggested as an effective method to suppress the expansion of BPDs in the substrate 28 31 .…”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23][24] Therefore, a remaining issue for bipolar degradation is the expansion of BPDs in substrates. [25][26][27] Inserting a "recombination enhancing layer" between a drift layer and a substrate has been suggested as an effective method to suppress the expansion of BPDs in the substrate. [28][29][30][31] This layer enhances the recombination probability of electronhole pairs in the epitaxial layer and decreases the number of electron-hole pairs at the BPDs in the SiC substrate.…”
Section: Introductionmentioning
confidence: 99%